Convenience and satisfaction: mediation of fairness and quality. Issue 5 (25th April 2016) - Roy, Sanjit Kumar; Lassar, Walfried M.; Shekhar, Vaibhav
ABSTRACT: This study investigates the role of service fairness and service quality in the relationship between service convenience types (decision, access, transaction, benefit and post-benefit) and customer satisfaction. Results show that service convenience has a significant positive impact on service fairness. Both service fairness and service quality mediate the relationship between service convenience and customer satisfaction. This study provides useful insights to both researchers and practitioners on the role of service convenience in improving service fairness, service quality and customer satisfaction. Findings of this study contribute to the literature by empirically investigating the impact of service convenience types on service fairness, service quality and customer satisfaction; and by examining the mediating role of service fairness and service quality between convenience types and customer satisfaction.